Pengaruh Fasilitas Wisata, Harga, Dan Aksesibilitas Terhadap Minat Berkunjung Ulang Pada Desa Wisata Brubuh Kecamatan Jogorogo - Hasna Aqilah Junila Putri; Hartirini Warnaningtyas; Mintarti Indartini (Universitas Merdeka Madiun, 2025)
Indonesia is a country with a diverse range of natural and man-made tourist attractions. From a tourism perspective, our country boasts numerous attractions, some of which are unmatched by other countries. This study aims to determine the influence of tourist facilities, price, and accessibility on revisit intention at Brubuh Tourism Village, Jogorogo District. The research method used was quantitative. The sample was determined using purposive sampling with a sample size of 100 respondents. Data collection used an online questionnaire using Google Forms. Data analysis used multiple linear regression analysis. The results of the study indicate that: 1) Tourism facilities (X1) have a partial effect on revisit interest in Brubuh Tourism Village, Jogorogo District, 2) Price (X2) has a partial effect on revisit interest in Brubuh Tourism Village, Jogorogo District, 3) Accessibility (X3) has a partial effect on revisit interest in Brubuh Tourism Village, Jogorogo District, 4) Tourism facilities, price, and accessibility simultaneously influence revisit interest in Brubuh Tourism Village, Jogorogo District.